PENGARUH AUDITOR SWITCHING DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Gunawan, Merylin Denisa; Suryanto, Suryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this research is to obtain empirical evidence regarding the effect of independent variables on the dependent variable. The independent variables used in this research are firm age, audit quality, leverage, profitability, firm size, and auditor switching. Meanwhile, the dependent variable used is earnings management. The object used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 until 2023. The sample selection method used purposive sampling with predetermined criteria. There are 80 companies that meet the criteria with a total of 240 data. This research used multiple regression analysis to analyze the data. The results of this research shows that firm age and auditor switching has a negative effect on earnings management. On the other hand, audit quality, leverage, profitability, and firm size has no effect on earnings management.